Virtual patient simulation in pharmacy education: A systematic review - Beshir, Semira Abdi; Mohamed, Affana Parveen; Soorya, Aadith; Sir Loon Goh, Sheron; Moussa El-Labadd, Eman; Hussain, Nadia; Said, Amira S.A. (Pharmacy Education, 2022)
Background: This review summarises the impact of virtual patient simulation (VPS) on pharmacy students’ knowledge, skills, and perceptions. Methods: The PubMed, Cochrane Library, and Web of Science databases were searched using relevant keywords. Full-text articles in English, published between 2010 and August 2021, were retrieved if they evaluate the impact of web-based interactive VPS in pharmacy education. Results: This review included 19 studies, 9 of which were comparative. VPS was used to develop or assess different pharmacy-related skills. In general, post-VPS exposure test scores were better than the pre-VPS test scores in 12 studies. VPS significantly improved higher-level learning, counselling, and decision-making skills more than paper-based cases. The favourable impact of VPS on learners’ confidence, student engagement, and satisfaction was noted. Conclusion: VPS enhances knowledge and clinical decision-making skills. It can also address the needs of pharmacy students with active learning preferences.